Medicinal Chemistry and Drug Discovery: A Review of Recent Advances and Multidisciplinary Approaches - Lal, Jaggi (AG Volumes, 2025)
The goal of the dynamic area of drug development is to find new therapeutic molecules to treat a variety of illnesses. In order to provide patient-centered care, healthcare experts from several disciplines collaborate via the multidisciplinary approach. This article reviews the many studies on the latest developments and interdisciplinary methods in drug discovery and medicinal chemistry. This review highlight that the medicinal chemistry and drug discovery have undergone transformative advancements through multidisciplinary collaborations and technological innovations. BTA-based compounds have shown broad therapeutic potential, including anticancer, antibacterial, and anti-inflammatory properties. The integration of artificial intelligence, machine learning, high-throughput screening, and rational drug design has accelerated drug development. Targeted therapies, gene-based treatments, and nanotechnology-driven drug delivery systems have improved efficacy and patient compliance. Collaborative efforts among chemists, pharmacologists, and clinicians enhance treatment outcomes, minimize toxicity, and address unmet medical needs. This multidisciplinary approach fosters innovation, clinical standardization, and improved healthcare delivery, ultimately leading to more effective, personalized, and patient-centered therapies.